Detection and analysis of microfibers and microplastics in wastewater from a textile company - YALÇIN, BAHATTİN; AKYILDIZ, SİNEM HAZAL (My University, 2022)
Textile wastewater is polluted by inorganic/organic substances, polymers, dyes, and microfibers (MFs), which are microplastics (MPs) and natural fibers. This work is aimed at the preliminary investigation of MFs and MPs in textile industrial wastewater, and at evaluating the removal efficiency of an on-site wastewater treatment plant (WWTP). Ten samples of inflows and outflows of the WWTP of a textile company (applying a physic-chemical process) have been analyzed. Firstly, the samples underwent a pretreatment with 15% hydrogen peroxide at 25◦C for 5 days to remove organic compounds. Secondly, the MFs were recovered from the aqueous phase by pre- screening centrifugation, density separation, and filtration as alternative options. Filtration obtained the best performances, compared to the other recovery processes. Thirdly, the MFs were counted through optical microscopy and the MPs were identified through micro-FTIR. The MFs amount in the inflow samples was in the range of 893–4452 MFs/L. The outflow samples (310–2404 MFs/L) exhibited a 38–65% reduction compared to the inflows, demonstrating that up to 62% of residual MFs can enter the sewer network or the receiving water body. Cotton and wool, and numerous MPs (acrylic, polyester, polypropylene, polyamide, and viscose/rayon) were identified in the inflow and outflow samples (with the only exception of \"dense\" viscose (rayon), not detected in the out- flows, and probably retained by the WWTP with the sludge). This study, even if just preliminary, offers interesting hints for future research on MFs/MPs detection in textile wastewater, and on the performance of a full-scale WWT process for their removal.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES